Incidence, alternative hosts, and molecular diversity of rice tungro viruses in Bali, Indonesia - LISTIHANI LISTIHANI; GUSTI NGURAH ALIT SUSANTA WIRYA; TRISNA AGUNG PHABIOLA; I MADE SUDARMA; I WAYAN SUANDA; DEWA GEDE WIRYANGGA SELANGGA; I GEDE RAI MAYA TEMAJA; WAFA’ NUR HANIFAH; RESTIANA MAULINDA; NI NYOMAN SISTA JAYASANTI; HERU ANGGARA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Listihani L, Wirya GNAS, Phabiola TA, Sudarma IM, Suanda IW, Selangga DGW, Temaja IGRM, Hanifah WN, Maulinda R, Jayasanti NNS, Anggara H. 2026. Incidence, alternative hosts, and molecular diversity of rice tungro viruses in Bali, Indonesia. Biodiversitas 27 (7): d270723. https://doi.org/10.13057/biodiv/d270723. Tungro disease is a significant threat to rice cultivation in Indonesia. The investigation of the presence of tungro viruses has never been reported in 9 districts and cities in Bali Province, Indonesia. This study aimed to analyze the incidence and severity of tungro disease, vector population density, the presence of weeds as alternative hosts, and the molecular character of Bali isolates. Research methods included sampling, observing the incidence and severity, analyzing population density of green leafhoppers, detecting RTBV and RTSV, DNA cloning, and sequencing analysis. The incidence and severity of tungro disease in Bali ranged from 80% to 100% and 28.49% to 64.73%, respectively. Population densities of Nephotettix virescens and N. nigropictus ranged from 5 to 20 and from 0 to 4 individuals per 10 double swings at each location. Eight weed species (Echinochloa crus-pavonis, Fimbristylis miliacea, Cyperus iria, Pontederia vaginalis, Ludwigia adscendens, L. octovalvis, Sphenoclea zeylanica, and Digitaria sanguinalis) were positive for tungro virus infection. The highest homology of RTBV and RTSV Bali isolates with Lombok isolates ranged from 98.0% to 98.7% and from 97.5% to 98.1%. RTBV and RTSV have disseminated across Bali. Based on coat-protein gene analysis derived from a small selection of clones, it indicates that these Bali isolates exhibit minimal genetic variation compared to other isolates from Indonesia.